PENERAPAN MODEL PEMBELAJARAN SCRAMBLE BERBASIS POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA BIDANG STUDI SEJARAH KEBUDAYAAN ISLAM - Fitria, Dini; Andriesgo, Johan (J-PAI: Jurnal Pendidikan Agama Islam, 2019)
This study aimed to determine the application of powerpoint-based scramble learning models in improving student learning outcomes in the field of study of the History of Islamic Culture Class VII One in Madrasah Tsanawiyah PP. Nurul Islam Kampung Baru. This research is a classroom action research, namely research that is practical, situational and contextual based on the problems that arise in learning activities in the field of study of the History of Islamic Culture in Madrasah Tsanawiyah PP. Nurul Islam Kampung Baru. Based on the research conducted, it can be concluded that the implementation of learning the History of Islamic Culture by applying the powerpoint-based scramble learning model is carried out by steps namely: pre-learning, initial activities, core activities, and concluding. After applying the powerpoint-based scramble learning model in class VII One in Madrasah Tsanawiyah PP. Nurul Islam Kampung Baru shows there is an increase in student learning outcomes. This can be seen from, before the action of the class average reached 71.30 and only 9 students or 39.13% who achieved mastery learning, but in the first cycle, using the power point scramble learning model increased with an average the class reached 76.39 and there were 15 students or 65.22% who achieved mastery learning, and the increase continued in the second cycle with the class average reaching 85.74 and 22 students or 95.65% who achieved mastery learning.Keywords: Implementation, Scramble Model, Powerpoint, Learning Outcomes